IL-9 Inhibits Viral Replication in Coxsackievirus B3-Induced Myocarditis - Yu, Miao; Long, Qi; Li, Huan-Huan; Liang, Wei; Liao, Yu-Hua; Yuan, Jing; Cheng, Xiang (Frontiers in Immunology, 2016)
Myocardial injuries in viral myocarditis (VMC) are caused by viral infection and related autoimmune disorders. Recent studies suggest that IL-9 mediated both antimicrobial immune and autoimmune responses in addition to allergic diseases. However, the role of IL-9 in viral infection and VMC remains controversial and uncertain. In this study, we infected Balb/c mice with Coxsackievirus B3 (CVB3), and found that IL-9 was enriched in the blood and hearts of VMC mice on days 5 and 7 after virus infection. Most of IL-9 was secreted by CD8+ T cells on day 5 and CD4+ T cells on day 7 in the myocardium. Further, IL-9 knockout exacerbated cardiac damage following CVB3 infection, along with a sharp increase in viral replication and IL-17a expression, as well as a decrease in TGF-β. In contrast, repletion of IL-9 in Balb/c mice with CVB infection induced the opposite effect. Studies in vitro further revealed that IL-9 directly inhibited viral replication in cardiomyocytes by reducing coxsackie and adenovirus receptor expression, which might be associated with up-regulation of TGF-β autocrine effect in these cells. However, IL-9 had no direct effect on apoptosis in cardiomyocytes. Our data indicated that IL-9 played a protective role in disease progression by inhibiting CVB3 replication in the early stages of VMC.